SHORTENING AND THEIR FUNCTION IN MODERN ENGLISH - Унгутбаева, Г.Ш.; Асанова, А.Б. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
This article is devoted to the study of types of abbreviation and their function in Modern English and their usage in mass media, medical, informational and technical spheres. The practical part represents selection of examples from Modern English textbooks, newspapers and magazines and their analysis according to the types and functions.
Keywords: types of abbreviation and their function; medical; informational and technical spheres